Crystallization of silicon–germanium by aluminum-induced layer exchange. (12th January 2018) - Isomura, Masao; Yajima, Masahiro; Nakamura, Isao
Abstract: We have studied the crystallization of amorphous silicon–germanium (a-SiGe) by aluminum (Al)-induced layer exchange (ALILE) with a starting structure of glass/Al/Al oxide/a-SiGe. We examined ALILE at 450 °C, which is slightly higher than the eutectic temperature of Ge and Al, in order to shorten the ALILE time. We successfully produced c-SiGe films oriented in the (111) direction for 16 h without significant alloying. The thickness of Al layers should be 2800 Å or more to complete the ALILE for the a-SiGe layers of 2000–2800 Å thickness. When the Al layer is as thick as the a-SiGe layer, almost uniform c-SiGe is formed on the glass substrate. On the other hand, the islands of c-SiGe are formed on the glass substrate when the Al layer is thicker than the a-SiGe layer. The islands become smaller with thicker Al layers because more excess Al remains between the SiGe islands. The results indicate that the configuration of c-SiGe can be altered from a uniform structure to island structures of various sizes by changing the ratio of a-SiGe thickness to Al thickness.